Effects of Different Paclobutrazol-Cultar Concentrations on the Micropropagation of Sugarcane (Saccharum Officinarum) Variety CPCL99-4455 - Daniels, Dion; Panti, Nidia; Guerra, David; Williams, Stephen (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2018)
Sugarcane (Saccharum officinarum), being an important cash crop in Belize, accounts for 60% of agricultural exports providing employment for thousands of Belizeans. This research was carried out to determine the effects of different Paclobutrazol (PBZ-Cultar) concentrations used in the culture media on in vitro multiplication of sugarcane variety CPCL99-4455. Three PBZ-Cultar concentrations were tested and compared with the control. The parameters evaluated to determine the effects of PBZ-Cultar were average height, number of dead leaves and multiplication coefficient. The plants from this experiment were planted in the acclimatization phase to determine if the use of PBZ-Cultar had any effect of the growth and development of the plants ex vitro. The results revealed that the culture medium supplemented with 0.08% PBZ-Cultar concentration had the best results both in the multiplication phase as well as the acclimatization phase.